Ants engaged in cooperative food transport show anticipatory and nest-oriented clearing of the obstacles surrounding the food: goal-directed behavior emerging from collective cognition - Fonio, Ehud; Mersch, Danielle; Feinerman, Ofer (Frontiers in behavioral neuroscience, 2025)
One of the hallmarks of higher cognition is the ability to anticipate near-future events and effectively react to them. This requires perceiving events in a dynamic environment and adjusting the actions accordingly to suit the expected outcomes. Social insects exhibit various forms of emergent collective cognition; however, it is not clear whether such preplanning is one of them. We discovered that when longhorn crazy ants cooperatively carry a large food item to the nest, some ants clear the path ahead of the moving load from small debris. The obstacle clearing is nest-oriented, as it creates a clear path connecting the food load with the nest. We show that this anticipatory obstacle-clearing behavior is context specific and that it is functional in reducing the time needed to deliver the large food load to the nest. Importantly, we found that no personal knowledge of the food load is required for the ants to start clearing the obstacles. Individual ant tracking revealed that clearing is instead triggered by social cues in the form of freshly laid pheromone markings. Indeed, we observed that obstacle clearing was performed by ants that had never experienced the big food load and even in cases where no such load was present at all, in response to the pheromone marks alone. These results provide strong evidence that individual ants do not possess an internal representation of the final goal of obstacle clearing. On the other hand, the goal-directedness of obtacle clearing appears to emerge at the ant group level from collective cognition.